"Systematic Combining": An approach to case research. Issue 4 (2nd October 2017) - Dubois, Anna; Gadde, Lars-Erik
Abstract: "Systematic combining" is a non-linear, non-positivistic, approach to case study research. The paper describes the central features of this research framing with regard to two basic processes: matching and direction/re-direction. These processes impact, and are affected by, two significant forms of interplay: theory vs. empirics, and the analytical framework vs. the evolving case. Major diversities in relation to the mainstream literature on case studies are discussed with regard to the perspective on the research process, the view of multiple and single case studies, the relevance of replication and generalization, and the role of the context. Moreover, three current challenges for qualitative research are identified. First, increasing methodological specialization and sophistication tend to disintegrate methodology from the important linkages to theory and research phenomenon. Second, mainstream requirements for replication and generalization lead to isolation of the research phenomenon from the empirical context, thus undermining the main advantage of the case study approach. Third, in order to improve the scientific recognition of qualitative case studies, researchers need to develop their abilities to convince readers about the relevance of their findings by providing better accounts for the research approach applied.